Endoscopic Removal of an Embedded Foreign Body Using Fluoroscopy - Yujin Lee; Yong Hwan Kwon (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Cases of foreign body ingestion are frequently seen in gastroenterology. However, it is not common for the foreign body to be located in the submucosa, which obscures it from view, even during endoscopy. A 74-year-old woman visited the emergency room 10 days after swallowing an implant screw during an implant procedure at a dental clinic. Abdominal CT revealed a 14-mm-long radio-opaque screw in the posterior wall of the proximal body of the stomach. On endoscopy, the screw was not observed in the stomach; however, fluoroscopic examination revealed that it was located under the mucosa of the posterior wall of the proximal body of the stomach. The screw was grasped using alligator forceps and retrieved. There was no evidence of perforation on chest radiography. Herein, we present a case wherein a foreign body embedded under the mucosa was removed.